2013
DOI: 10.1080/09540121.2012.750710
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV among those 15 and older in rural South Africa

Abstract: A greater knowledge of the burden of HIV in rural areas of Southern Africa is needed, especially among older adults. We conducted a cross-sectional biomarker survey in the rural South African Agincourt Health and Sociodemographic Surveillance site in 2010–2011 and estimated HIV prevalence and risk factors. Using an age–sex stratified random sample of ages 15 +, a total of 5037 (65.7%) of a possible 7662 individuals were located and 4362 (86.6%) consented to HIV testing. HIV prevalence was high (19.4%) and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 189 publications
(205 citation statements)
references
References 6 publications
5
197
3
Order By: Relevance
“…We used the first in this paper to clarify the population of interest, and those included in the study. 2 While the rates of HIV prevalence among older women are lower than those of their younger counterparts, a growing body of literature indicates the importance of tracking the aging of the HIV epidemic , Hontelez et al 2011, Mills et al 2012, Gómez-Olivé et al 2013. 3 The Gogo Project received Institutional Review Board clearance for Human Subjects Research for data collection from the University of Colorado and the University of the Witwatersrand, and for analysis of existing data from the University of Missouri.…”
Section: Resultsmentioning
confidence: 99%
“…We used the first in this paper to clarify the population of interest, and those included in the study. 2 While the rates of HIV prevalence among older women are lower than those of their younger counterparts, a growing body of literature indicates the importance of tracking the aging of the HIV epidemic , Hontelez et al 2011, Mills et al 2012, Gómez-Olivé et al 2013. 3 The Gogo Project received Institutional Review Board clearance for Human Subjects Research for data collection from the University of Colorado and the University of the Witwatersrand, and for analysis of existing data from the University of Missouri.…”
Section: Resultsmentioning
confidence: 99%
“…Thus the plausibility of field notes collected by LRAs can only be assessed by virtue of their persuasiveness (Angotti and Kaler 2013;Watkins and Swidler 2009). Given the prevalence of HIV in Agincourt (19%) (Gómez-Olivé et al 2013), however, and the extent to which the epidemic is discussed on radios, in the newspapers, and in social marketing efforts throughout the country, everyday talk about HIV/AIDS is commonplace. As Audrey, one of the Conversations" LRAs remarked during the course of the study, "People are talking [about AIDS].…”
Section: Discussionmentioning
confidence: 99%
“…10 The project drew its inspiration from research spearheaded by Susan Watkins in Malawi (Watkins and Swidler 2009). 11 The Conversations data collection followed a community-level HIV prevalence and sexual behavior study conducted in Agincourt the previous year, where HIV infection was estimated at 19% and around 45% in some age groups (Gómez-Olivé et al 2013). Conversations was designed to capture everyday discourses about AIDS to learn more about local social norms and cultural scripts surrounding the epidemic.…”
Section: Conversationsmentioning
confidence: 99%
“…[8] Truvada intervention will empower mostly young women to be in control of their infection status, as HIV prevalence and incidence rates remain disproportionately higher in females than in males. [9] However, as much as Truvuda is a potentially useful intervention, little is known about the drivers of product acceptability to end-users of such methods for HIV prevention. In a study that explored the end-user's product preference for multipurpose prevention technology delivery forms in SA and Kenya, it was found that only 27% of women aged 18 -30 years preferred the Truvada.…”
Section: In Practicementioning
confidence: 99%